Virtual Playground: An Augmented Reality Application to Improve English Learning - Pereira, Luis; da Silva, Manoela; Roberto, Rafael Alves; Teichrieb, Veronica; Cavalcante, Patricia Smith (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
Augmented Reality applications for education change the classroom experience for both teachers and students. However, the use of these tools are not widespread yet. The applications still have some limitations, such as: hard to use interfaces, lack of freedom to create content, lack of support for a shared experience and many others. To tackle these problems, this work presents the process of ideation, implementation and testing of Virtual Playground, an application collaboratively created with language teachers, designers and engineers. This work presents results regarding what are the main teachers' needs that developers and researchers have to take into account: intuitive interface, freedom to create and reuse virtual content, an offline version to avoid infrastructure limitations, etc. It also presents the concept validation by teachers and the confirmation that an AR application can be used in different stages of a lesson.